2022
DOI: 10.3390/rel13080675
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude to God Predicts Religious Well-Being over Time

Abstract: The authors used a prospective design to investigate how gratitude to God predicts religious well-being over time. Gratitude to God is a central aspect of monotheistic religions, and thus may be particularly important to the religious/spiritual well-being of believers. Participants completed online measures of trait and state gratitude to God, along with spiritual well-being, nearness to God, and religious commitment scales over a one-to-two-month period. General well-being, trait gratitude, and the Big Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…We suspect that both might be true: GTG and one’s experiential conception of a loving God may interact in a positive feedback loop. One study found that trait GTG predicted enhanced nearness to God over time (P. C. Watkins et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suspect that both might be true: GTG and one’s experiential conception of a loving God may interact in a positive feedback loop. One study found that trait GTG predicted enhanced nearness to God over time (P. C. Watkins et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…But GTG may be particularly important to spiritual well-being. In a recent prospective study, trait GTG predicted increased spiritual well-being over time (P. C. Watkins et al, 2022). In sum, God is an important benefactor for religious people, GTG is a frequent emotion for believers in God, and GTG may be important for the general and spiritual well-being of religious/spiritual individuals.…”
Section: Gratitude To Godmentioning
confidence: 92%
See 1 more Smart Citation
“…In many religious systems and spiritual paths, gratitude is treated as a desired value and virtue (Carlisle & Tsang, 2013 ; Emmons & Kneezel, 2005 ). In a religious context, human beings should be grateful to God as a source of all good (Watkins et al, 2022 ). A grateful attitude to God, who is perceived as a benefactor, is enhanced by a cultural reciprocity norm (Gouldner, 1960 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for religiosity, much research has shown that increasing commitment to religion is associated with better health outcomes (Shattuck & Muehlenbein, 2020). This has included lower levels of self-reported depression (Forouhari et al, 2019), anxiety (Abdel-Khalek et al, 2019), and personality disorders (Buzdar et al, 2019), in addition to higher rates of well-being (Hoogeveen et al, 2022), gratitude (Watkins et al, 2022), hope (Counted et al, 2022), and supportive connections with God and others (Lloyd & Reid, 2022). That being said, an existing body of research has also suggested that religious individuals are possibly less likely to come forward for mental health help when facing psychological difficulties (Lloyd et al, 2021; Lloyd & Kotera, 2021).…”
mentioning
confidence: 99%